Drift into Failure: From Hunting Broken Components to Understanding Complex Systems - Dekker, Sidney (CRC Press, 2011)
This book explores complexity theory and systems thinking to better understand how complex systems drift into failure. It studies sensitive dependence on initial conditions, unruly technology, tipping points, diversity - and finds that failure emerges opportunistically, non-randomly, from the very webs of relationships that breed success and that are supposed to protect organizations from disaster. It develops a vocabulary that allows us to harness complexity and find new ways of managing drift.